أسباب ورود الحديث، المفهوم، والنشأة، والضرورة. - عوني م. ياسر هنر; سليمان أ.م.د ابراهيم احمد (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
The study "The Reasons for the Revelation of the Hadith (Concept, Origin, and Necessity)" focused on the idea of the reasons for the revelation of the hadith and the various definitions that scholars have of it. It was discovered from these definitions that the science of the reasons for the revelation of the hadith (a science that searches for the circumstances, circumstances and events that caused the hadith), as the study included information on the development of the hadith. According to the jurists of the noble Companions, this science and its origin date back to the first century AH, but it wasn’t until the fourth century AH that it emerged as a separate discipline with its own set of rules and branches. Further study demonstrates the significance of this science in developing solid knowledge of the Prophet’s Sunnah text as well as sound reasoning. The research extracts the most significant findings it obtained on extremism and carelessness, as it aids in the development of purposeful thinking, and in conclusion, suggests the most significant suggestions with regard to this science.